Strategic mapping of iterative technology development based on modular analysis of modification quality indicators - M. N. Mityagina; S. V. Murashova (Омский научный вестник)
The article presents the results of the technical facilities development at the stages of the product life cycle. Using elementary development functions, a description of the transitional phases of modification in the process of existence is given. As a result of which, a conclusion is drawn about the inevitable obsolescence of the object as a result of the influence of natural factors. To offset the degradation of engineering facilities, it is necessary to initiate innovative processes aimed at adding value to the product. Innovation is based on a target vector or strategy that describes the operations and resources needed to achieve a planned result. To form a strategy for managing the development of a technological solution, it is proposed to use a modular method for analyzing quality indicators based on the study of situational, retrospective and predictive indicators described using three types of maps: innovation flow, technological gaps and frontiers. As a result of the construction of these maps, a comprehensive understanding is formed of the nature of technology improvement and the prospects for its development, implemented in several iterations.